Development and Experimental Evaluation of a VR Based Cooperative Learning Model for the Human Circulatory System - Hasanuddin Hasanuddin; Abd Kahar; Jong Soo Ri; Diogo Lopes (Journal of Paddisengeng Technology, 2026)
Background. The human circulatory system is a complex biological topic that requires students to understand spatial structures and dynamic blood flow processes. Conventional instruction often provides limited opportunities for immersive visualization and structured collaboration. Purpose. This study aimed to develop and evaluate a Virtual Reality Based Cooperative Circulation Learning Model (VR CCL) to improve Grade XI students’ biology learning outcomes. Method. The study employed a research and development design based on the ADDIE model, followed by a quasi experimental pretest–posttest nonequivalent control group design. The participants were 52 students from two intact classes at a senior high school in Enrekang Regency, Indonesia. Data were collected using expert validation sheets, practicality questionnaires, observation sheets, and biology achievement tests. Novelty. The model integrates immersive VR exploration with structured cooperative roles, group investigation, concept reconstruction, presentation, and individual evaluation. Results. The model achieved an overall Aiken’s V coefficient of .91. Teacher and student practicality scores reached 91.50% and 88.70%, respectively. The experimental group obtained a higher posttest mean than the control group (73.76 vs. 64.52), with a significant adjusted group effect, F(1, 49) = 19.38, p < .001. Conclusion. VR CCL was valid, practical, and effective in improving students’ learning outcomes on the human circulatory system.